2014
DOI: 10.5194/acp-14-3945-2014
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in the upper stratospheric ozone at Syowa, Antarctica

Abstract: Abstract. Analyses of stratospheric ozone data determined from Dobson-Umkehr measurements since 1977 at the Syowa (69.0 • S, 39.6 • E), Antarctica, station show a significant decrease in ozone at altitudes higher than that of the 4 hPa pressure level during the 1980s and 1990s. Ozone values over Syowa have remained low since 2001. The time series of upper stratospheric ozone from the homogenized NOAA SBUV (Solar Backscatter Ultraviolet Instrument)(/2) 8.6 overpass data (±4 • , 24 h) are in qualitative agreemen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 104 publications
(146 reference statements)
0
9
0
Order By: Relevance
“…Because O 3 variability in the upper polar stratosphere is mainly driven by chemistry, this region is commonly used for the detection of ozone hole recovery [ Miyagawa et al ., ]. The results of this study suggest that EPP‐induced O 3 variations on a decadal time scale might be of importance in the analysis of upper stratospheric O 3 trends.…”
Section: Discussionmentioning
confidence: 99%
“…Because O 3 variability in the upper polar stratosphere is mainly driven by chemistry, this region is commonly used for the detection of ozone hole recovery [ Miyagawa et al ., ]. The results of this study suggest that EPP‐induced O 3 variations on a decadal time scale might be of importance in the analysis of upper stratospheric O 3 trends.…”
Section: Discussionmentioning
confidence: 99%
“…Trends are statistically different from zero at the 95% confidence interval above 330 K (~11 km). A recent study using ground-based UV reflectance (Umkehr) measurements capable of detecting ozone averaged over 5–10 km thick layers in the Antarctic showed similar values of about −2 to −3%/year at the lower stratospheric Umkehr layers 32 .
Figure 2Vertical structure of Antarctic ozone recovery: ( a ) The ozone trends estimated from ozonesonde data in the Antarctic vortex in spring (SON) with ≥65° S EqL criterion (“standard”, black cures), Nash et al . 20 vortex criterion (“Nash-96”, blue curves) and without considering the vortex boundaries (“no VORTEX”, red curves) for the 1979–2001 (dash) and 2001–2013 (solid) periods.
…”
Section: Drivers Of Ozone Change and Past Trendsmentioning
confidence: 97%
“…It has been reported that the mean age of air in the Antarctic upper stratosphere and lower mesosphere reached 10 years (Stiller et al 2008). Miyagawa et al (2014) showed that assuming 10 years of age of air gave the best fit of ODS trend to ozone concentration in the upper stratosphere and lower mesosphere over Antarctic Syowa Station. Figure S3 shows the composite differences obtained by taking a break point at 2005 instead of 1995.…”
Section: Discussionmentioning
confidence: 99%